Benda Asing di Esofagus - Wina Andria; Baluqia Iskandar Putri (Jurnal Anestesi, 2025)
Foreign objects in the esophagus are one of the emergencies in the field of ENT-KL that often occur and can be found at all ages throughout the world is swallowed foreign objects. Children under 5 years of age most often enter the ER because of foreign objects stuck in their esophagus, the most common symptoms are a history of choking, discomfort or pain in the area above the clavicle in the right or left trachea that gets worse when swallowing, dysphagia. There are many techniques for extracting foreign objects in the esophagus, but it is necessary to pay attention to the indications and possible complications. Based on research, the prognosis of foreign objects in the esophagus is 80-90% very good as long as no complications have occurred.